The Effectiveness Of Counterpressure With Effleurage Massage On Labor Pain - Meli Doloksaribu; Emi Br Barus; Muryani; Lidia Fitrayani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Pain is a different personal and subjective experience for each individual, including in childbirth. Pain during childbirth, caused by uterine contractions, cervical dilatation and perineal distension. Pain management can be done in two ways, namely pharmacological and non-pharmacology. The non-pharmacological methods are massage counterpressure and massage effleurage. Objective: to find out the difference in the effectiveness of massage counterpressure and massage effleurage on labor pain at the UPTD Longkib Health Center, Subulussalam City. Methods: This research was carried out at the Longkib Health Center which used the Quasi Experiment research method with a pre-test post-test control design approach. Sample selection was carried out by consecutive sampling technique, the sample number was 20 respondents (10 respondents for counterpressure massage and 10 respondents for massage effleurage). The pain measurement used, namely the Numeric Rating Scale (NRS), was then processed in the SPSS computer program version 22. Results: Data were processed using the Mann-Whitney test with the result p value = 0.009. This shows that the value of p < ?, then the null (Ho) hypothesis is rejected and the alternative hypothesis (Ha) is accepted. Conclusion: that massage counterpressure is more effective than massage effleurage for lowering labor pain.